Comparing the work values of engineers with managers, production and clerical workers : a multivariate analysis - Shapira, Zur [Verfasser]; Griffith, Terri L. [Verfasser] (My University, 1990)
"Engineers and scientists have been compared in previous research on their work attitudes. Conceivably the interest in comparing these two groups of professionals was a result of the joint work they often do in research and development departments. The present framework suggests that engineers who work in production departments would have work values and attitudes which would be more similar to those of managers. Survey data was collected from 432 employees in two industrial corporations in Israel. Profile analysis showed that the work values of engineers were similar to those of managers and different from those of production and clerical workers. Furthermore, work values were also related to behavioral outcomes such as performance and tardiness. Implications regarding the study of engineering as a profession and the use of work values in organizational reserach are discussed." (author's abtract) ((en)) In einer vergleichenden Analyse werden die Arbeitseinstellungen von Ingenieuren, Managern, Arbeitern und Angestellten untersucht. Dazu wurden Interviews mit 432 Beschäftigten aus zwei industriellen Unternehmen in Israel durchgeführt. Die Profilanalyse zeigt, dass die Arbeitswerte der Ingenieure denen der Manager ähnlich sind und sich von denen der Arbeiter und Angestellten unterscheiden. (IAB)
Vergleich von Arbeitseinstellungen bei Ingenieuren mit Managern, Arbeitern und Angestellten
Keywords: S 6.3.1 Ingenieurberufe, Chemiker, Physiker, Mathematiker; G Gesellschaftlicher Kontext; Ingenieur; Führungskraft; Arbeiter; Angestellter; Einstellung; Arbeit; Berufsproblem; Quantitative Angaben